Pengujian kualitas informasi laporan keuangan pada organisasi perangkat daerah - Widodo, Sri; Maharani, Ria Resti (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2021)
This aim of this research to know the effect of human resources quality, information technology utilization, internal control systems and supervision of the reliability and timeliness in regional financial reporting. The research was done in Organisasi Perangkat Daerah OPD Bantul. The obtained by questionnaires distributed to 129 respondents employee of the finance / accounting department. The method used in this research is multiple linear regression method. The results shows that first the of human resources quality, internal control systems, and supervision is significantly affected to the reliability and timeliness of regional financial reporting. Both the human resources quality, information technology utilization, and supervision do not affected to the reliability and timeliness of regional financial reporting. Keywords: human resources quality, information technology utilization, internal control systems, supervision, reliability and timeliness